Pengawasan Partisipatif Sebagai Upaya Menciptakan Siaran Sehat dan Berkualitas Di Provinsi Bengkulu - Fonika Fonika; Gushevinalti Gushevinalti; Lisa Adhrianti (JIKA (Jurnal Ilmu Komunikasi Andalan), 2021)
This research is entitled "Participatory Monitoring as an Effort to Create Healthy and Quality Broadcasts in Bengkulu Province". The purpose of this study is to understand the concept of participatory monitoring of broadcast content by the public, both on television and radio. Furthermore, participatory supervision will encourage the public to participate in determining healthy and quality broadcast content. A qualitative approach with a descriptive method is used as a reference for writing articles, because the data studied are in the form of social realities. The results of the study indicate that in controlling the content of state television and radio broadcasts, independent state institutions have been established at the Center and the Regions, namely KPI and KPID. The number of KPID commissioners is limited to only 7 (seven) people assisted by limited staff and monitoring staff with their main tupoksi. Not to mention that broadcasting institutions spread throughout Bengkulu Province are still monitored manually, have not used streaming technology and the majority of broadcasting institutions have not adapted to technological changes in the current digitalization era. Broadcasting institutions have not yet carried out media convergence that can be accessed on various new media platforms quickly. So this condition certainly requires the participation of the community as participatory supervision to become an extension of the eyes and ears of the Bengkulu KPID. Strengthening media literacy for audiences is a necessity, so that audiences have the competence to be able to understand which broadcast content is good and which is not. If the audience already has the competence to receive information or known as media literacy and in the end they will be empowered in front of the media.